Design and control of underwater robot system for sea cucumber fishing. (10th February 2022) - Shi, Xinxin; Zhu, Chenyang; Lu, Pengcheng
Sea cucumber fishing is an important application of underwater robots. In order to realize the function of sea cucumber fishing, an underwater robot system for sea cucumber fishing is designed, which can reduce operation requirements and costs while realizing sea cucumber fishing. The overall system plan includes the design of subsystems such as power supply system, fishing system, transmission system, propulsion system, balance and positioning system, and anti-collision airbag. According to the actual needs of sea cucumber fishing, the mechanical structure and size of each subsystem are designed, and SolidWorks is used to complete the three-dimensional modeling of the overall system. The sliding mode control and adaptive sliding mode control algorithms are used to compare the positioning control effects of the underwater vehicle to verify the effectiveness of the system design.